2019
DOI: 10.14814/phy2.14249
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and barrier responses of human airway epithelial cells exposed to cannabis smoke

Abstract: Globally, many jurisdictions are legalizing or decriminalizing cannabis, creating a potential public health issue that would benefit from experimental evidence to inform policy, government regulations, and user practices. Tobacco smoke exposure science has created a body of knowledge that demonstrates the conclusive negative impacts on respiratory health; similar knowledge remains to be established for cannabis. To address this unmet need, we performed in vitro functional and transcriptomic experiments with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
2
28
1
Order By: Relevance
“…Vero E6 cells (African green monkey cells; ATCC, https://www.atcc.org) were maintained in Dulbecco’s modified Eagle’s media (DMEM) supplemented with 10% fetal bovine serum (FBS; Sigma-Aldrich, https://www.sigmaaldrich.com), 1x L-Glutamine and Penicillin/Streptomycin (Pen/Strep; Corning, https://ca.vwr.com). Calu-3 cells (human lung adenocarcinoma derived; ATCC, https://www.atcc.org) were cultured as previously mentioned (4). THF cells (human telomerase life-extended cells) were cultured as previously mentioned (5).…”
Section: Methodsmentioning
confidence: 99%
“…Vero E6 cells (African green monkey cells; ATCC, https://www.atcc.org) were maintained in Dulbecco’s modified Eagle’s media (DMEM) supplemented with 10% fetal bovine serum (FBS; Sigma-Aldrich, https://www.sigmaaldrich.com), 1x L-Glutamine and Penicillin/Streptomycin (Pen/Strep; Corning, https://ca.vwr.com). Calu-3 cells (human lung adenocarcinoma derived; ATCC, https://www.atcc.org) were cultured as previously mentioned (4). THF cells (human telomerase life-extended cells) were cultured as previously mentioned (5).…”
Section: Methodsmentioning
confidence: 99%
“…Inhaled cannabis smoke travels through the upper and lower airways, with airway epithelial cells being a major site of first contact. We have demonstrated with an in vitro model of airway epithelial cell culture that cannabis smoke induces a concentration-dependent reduction in airway epithelial cell viability, barrier function, while promoting pro-inflammatory cytokine secretion (31, 32). Complementary profiling of human epithelial cells isolated via bronchial brushings has demonstrated cannabis consumption-dependent elevations in TLR5, TLR6, and TLR9 gene expression(101).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function(30-32). Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges(31, 32). However, the contribution of the endocannabinoid system to these observations has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…The log 2 fold change (FC) of would require repeated exposures over time in vitro. Despite this limitation, we emphasise that our previous publication using this model demonstrated strong significant correlations of gene expression with in situ bronchial brushes from human smokers and primary air-liquid interface cultures exposed to tobacco smoke [8]. Additional experiments using primary human airway epithelial cells grown under air-liquid interface culture conditions and exposed to whole-smoke extract should be explored to complement the present data.…”
mentioning
confidence: 85%
“…We next interrogated RNA sequencing data to address the efficacy of LABA/GC intervention on attenuating CSE-and TSE-induced transcriptomic responses observed in our previous study [8]. First, we observed that the most upregulated gene exclusive to Form/Bud treatment was HSD11B2 (corticosteroid 11-β-dehydrogenase) (vehicle+Form/Bud FC 34.80, CSE+Form/Bud FC 33.99 and TSE+Form/Bud FC 27.32), indicating that our intervention was efficacious on modulating glucocorticoid signalling (data not shown).…”
mentioning
confidence: 99%